KONSEP DIRI ANGGOTA KOMUNITAS PUNK DI KOTA PEKANBARU - Chicilia Christi; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The presence of the punk community in Pekanbaru, have a perception of punk ideology itself and is influenced by the concept of self to form the character of members of the punk community. Those who joined the punk community will certainly have a perception of punk itself and influenced by the concept of self is formed. The formation of self-concept is due to the interaction of behavior and communication, both verbal and nonverbal. self-concept formed by the interaction and communication that affects a person behave and communicate. This study aims to determine the self-image, self-esteem and the factors that influence the formation of self-concept punk community in the city of Pekanbaru.This study uses qualitative research methods to conduct phenomenological approach. Subjects in this study amounted to 13 people. Data collection techniques are grouped through participant observation, in-depth interviews, and documentation. This study uses a model of interactive data analysis Miles and Hubermen, by using a technique that checks the validity of the data through the extension of participation and triangulation.The results of this study indicate that the self-image that they feel are positive, because they are not harmful and do not disturb others. Self-esteem is high enough punk community members look of self-satisfaction they feel as punkers, they are happy with what they choose. Until the factors that influence on the punk community members family, friends and environment. Conclusion positive self-image visible although they viewed negatively from the appearance and use of symbols inherent in themselves. Esteem of members of the punk community is quite high, although many are abusive, berate, insult but it is felt not affect them. Factors affecting ie, family, friends, and environments that make up the character of the members of the punk community.Kata Kunci : Self Concept, Self Image, Self Esteem, Punk Community